IMPLIKASI PENGAJIAN IHYA ULUMUDDIN TERHADAP PERUBAHAN PRILAKU SANTRI - Fadlullah Fadlullah; Sutejo Sutejo; Jamali Jamali (CV. ADIBA AISHA AMIRA, 2023)
Humans who live in modern and millennial times like today are really faced with various kinds of tough world tests and temptations. Moral degradation, juvenile delinquency, globalization, westernization, hedonism, consumerism, and materialism are a series of world diseases that undermine human religious values, so that humans are only concerned with the outer aspects, while the inner aspects are eroded away. This research aims to analyze the implications of reciting the book of Ihya Ulumuddin on changes in students' behavior. The methodology used in this study is qualitative research with phenomenological and hermeneutic research types and uses a data analysis approach. According to Imam Al-Ghazali, there are two ways of educating morals, namely, first, getting used to practicing good deeds. Second, habituation is done repeatedly. Imam Al-Ghazali in his efforts to educate children has a special view. He focuses more on efforts to bring children closer to Allah SWT. According to what is contained in the book Ihya Ulumuddin Imam Al-Ghazali on page 154 argues that a student should humble himself to the teacher and glorify the teacher by obeying him, this is done for blessings in studying. The impact felt by the students after participating in the Ihya' Ulumuddin Book of Learning at the Kebon Jambu Al-Islamy Islamic Boarding School, that is, those who initially did not know morals after participating in the Ihya' Ulumuddin recitation became aware and able to apply it in everyday life, many felt positive changes that were originally Less respect for time becomes more disciplined, those who previously lacked respect for knowledge can now respect knowledge, those who were previously indifferent to friends are now more concerned and those who previously did not have a respectful attitude towards their teacher or kyai are now more respectful.